Analisis Pengaruh Keputusan Investasi, Profitablitas dan Likuiditas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sektor Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Laila Isnaini Hikmawati; Siti Aisyah Hidayati (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This quantitative study explores the determinants of firm value in property and real estate entities listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using a panel data regression model, the study examines the impact of investment decisions (proxied by FAR), profitability (proxied by ROA), and liquidity (proxied by CR) on firm value (proxied by PBV), while also testing the moderating effect of firm size (proxied by FZ). The results of the empirical analysis indicate that investment decisions have a positive and statistically significant effect on firm value. On the other hand, profitability and liquidity only show a positive but insignificant correlation. The company size variable failed to moderate the interaction between the independent and dependent variables, thus its role is limited as a potential moderator. The implications of this finding are relevant for stakeholders in formulating investment policies and corporate strategies aimed at enhancing value.